(untitled) (Global Journal of Medical Research, 2022)
People with Down syndrome DS present neurophysiological problems that could be alleviated with the systematic practice of Physical Education PE However there are questions regarding laboratory assessments for the prescription of exercises as there are no adequate equipment or protocols for this group the difficulty of the individual with DS concerning the proposed tests and difficulty in controlling emotions when in a laboratory environment because they present intellectual disability